(untitled) (NBPA Journal for Arts, Humanities & Social Sciences, 2025)
This paper delves into the core of Nyāya philosophy by exploring the sixteen categories (ṣoḍaśa-padārthas) outlined in Gautama’s Nyāya-sūtra and their pivotal role in achieving liberation (niḥśreyasa). While it provides the fundamentals of the ultimate goal, liberation (niḥśreyasa), it would also provide the foundation for why Nyāya philosophy is not merely a spiritual philosophy but has a longstanding logical setup for acquiring knowledge. Hence, the paper provides the philosophical and epistemological analysis underpinning the connection of the categories in the Nyāya-sūtra (1.1.1) for true knowledge (pramā) and how true knowledge helps in achieving liberation (apavargaḥ in Nyāya-sūtra-1.1.2 as the ultimate means of inquiry.